Comparison of macular buckling and vitrectomy for the treatment of macular schisis and associated macular detachment in high myopia: a randomized clinical trial. Issue 3 (17th November 2019) - Liu, Bingqian; Chen, Shida; Li, Yonghao; Lian, Ping; Zhao, Xiujuan; Yu, Xiling; Li, Tao; Jin, Chenjin; Liang, Xiaoling; Huang, Suber S.; Lu, Lin
Abstract: Objective: To compare the efficacy and safety of macular buckling and vitrectomy for myopic traction maculopathy showing macular schisis (MS) and associated macular detachment (MD) but without full‐thickness macular hole (FTMH). Design: Prospective, randomized, parallel, open‐label study. Methods: Patients were randomly assigned to either buckling or vitrectomy group. Macular buckling and intravitreal C3F8 gas injection were performed in the buckling group. Small gauge vitrectomy, internal limiting membrane peeling (ILMP) and C3F8 gas tamponade were performed in the vitrectomy group. The patients were followed for 12 months. Main outcome measures: Best‐corrected visual acuity (BCVA) at 12 months. Results: A total of 85 patients were randomized, 80 eyes were included (41 receiving buckling, 39 received vitrectomy), and 78 patients completed the study. There were less eyes determined as surgical failure and required a second surgery in the buckling group than vitrectomy the group (2.4% versus 18.4%, p = 0.021). After surgery, macular buckling achieved more improvement in BCVA (+21.7 versus +4.5 Early Treatment Diabetic Retinopathy Study (ETDRS) letters, p = 0.002). FTMH development was observed in only 1 (2.4%) eye, after removing of the implant due to recurrent conjunctival erosion, in the buckling group and 10 (26.3%) eyes (seven with‐, three without MD) in the vitrectomy group (p < 0.001). More eyes developed cataracts in the vitrectomy group than did in the buckling group (28.9% versus 7.5%, p = 0.014). Macular buckling‐associated strabismus (esotropia), binocular diplopia and implant exposure were observed in limited cases. Conclusions and relevance: Macular buckling is superior to vitrectomy with ILM peeling plus gas injection for surgical treatment of MS and associated MD in high myopia.